Translating Beowulf : modern versions in English verse - Magennis, Hugh (D.S. Brewer, 2011)
Translations of the Old English poem Beowulf proliferate, and their number continues to grow. Focusing on the particularly rich period since 1950, this book presents a critical account of translations in English verse, setting them in the contexts both of the larger story of recovery and reception of the poem and of perceptions of it over the past two hundred years, and of key issues in translation theory. Attention is also paid to prose translation and the the creative adaptations of the poem that have been produced in a variety of media, not least film. The author looks in particular at four translations of arguably the most literary and historical importance: those by Edwin Morgan (1952), Burton Raffel (1963), Michael Alexander (1973) and Seamus Heaney (1999). But, from an earlier period, he also gives a full account of William Morris's 1895 version.